3D Printing Ionogel Auxetic Frameworks for Stretchable Sensors. Issue 9 (8th August 2019) - Wong, Jitkanya; Gong, Alex T.; Defnet, Peter A.; Meabe, Leire; Beauchamp, Bruce; Sweet, Robert M.; Sardon, Haritz; Cobb, Corie L.; Nelson, Alshakim
Abstract: Ionogels are an emerging class of soft materials that exhibit ionic conductivity and thermal stability without the need to replenish ions or the addition of conductive particle fillers. An ionogel ink is reported for direct‐write 3D printing to fabricate conductive structures that can vary in the printed object geometries. This approach relies on a shear‐thinning ionogel ink that can be extruded to afford self‐supporting constructs. After a brief UV cure, the printed construct is transformed into a mechanically tough, transparent structure that is ionically conductive. Upon application of stretching and twisting loads, the 3D‐printed objects exhibit detectable changes in conductivity. To demonstrate the versatility of rapid prototyping with the ionogel inks, an auxetic structure is 3D printed and tested as a strain sensor. The printed auxetic structure exhibits an electrical response to strain, but also demonstrates increased extensibility and operational range in comparison to a casted bulk film with the same outer dimensions. Abstract : An ionogel comprised of modified F127‐based polymer and ionic liquid 1‐butyl‐3‐methylimidazolium tetrafluoroborate is presented. This shear‐thinning gel can be extruded and 3D printed via a direct‐write 3D printer to create complex 3D structures. Fabrication of an auxetic sensor is demonstrated to show the use of 3D printing to achieve the mechanical attributes desired in stretchable sensors.